Erasmus’ Edition of the Complete Works of Augustine - Tello, Joan (Erasmus studies, 2022)
This article offers a commented inventory of the complete works of Augustine that Erasmus published in 1528–1529. The inventory is preceded by an overview of Erasmus’ publications on the Fathers of the Church and previous editorial work on Augustine undertaken by other printers, which helps place the edition of Erasmus into context.